A REVIEW ON FAST-DISSOLVING ORAL FILM - kawale, Komal A; Neha B Autade; Narhare, Harshda s; Mhetrea, Raksha L (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Due to their increased comfort and flexibility, fast-dissolving oral films are the most cutting-edge oral solid dose form. It increases the effectiveness of APIs by dissolving in the oral cavity in under a minute after coming into touch with less saliva than fast-dispersing tablets, without chewing, and without the requirement for water for administration. Some patients, especially those who are young or elderly, have trouble chewing or swallowing solid dose forms. The fear of choking prevents many young and geriatric patients from taking these solid preparations. Consequently, orally dissolving pills have been developed. Due to consumer demand for a fast-dissolving product over conventional tablets or capsules, OTFs have gained a position as an alternative in the market. Depending on the film thickness and choice of the polymer matrix, these films can be adjusted to release the medicine more gradually. These films typically disintegrate in seconds to release the active ingredients. When a dosage form is placed on the tongue or in the oral cavity, it can swiftly hydrate, adhere, and dissolve, allowing for rapid local or systemic drug delivery. This type of dosage form is referred to as a film or strip.